A digital atlas of breast histopathology: an application of web based virtual microscopy. Issue 12 (24th November 2004) - Lundin, M; Lundin, J; Helin, H; Isola, J
Abstract : Aims: To develop an educationally useful atlas of breast histopathology, using advanced web based virtual microscopy technology. Methods: By using a robotic microscope and software adopted and modified from the aerial and satellite imaging industry, a virtual microscopy system was developed that allows fully automated slide scanning and image distribution via the internet. More than 150 slides were scanned at high resolution with an oil immersion ×40 objective (numerical aperture, 1.3) and archived on an image server residing in a high speed university network. Results: A publicly available website was constructed, http://www.webmicroscope.net/breastatlas, which features a comprehensive virtual slide atlas of breast histopathology according to the World Health Organisation 2003 classification. Users can view any part of an entire specimen at any magnification within a standard web browser. The virtual slides are supplemented with concise textual descriptions, but can also be viewed without diagnostic information for self assessment of histopathology skills. Conclusions: Using the technology described here, it is feasible to develop clinically and educationally useful virtual microscopy applications. Web based virtual microscopy will probably become widely used at all levels in pathology teaching.